The Development of Islamic Economic Thought and the Role of the DSN MUI on Musyarakah Mutanaqishah Products in Islamic Banking in Indonesia - Utami, Citra Kharisma (Ecobankers : Journal of Economy and Banking, 2025)
This article examines the development of Islamic economic thought related to Musharakah Mutanaqishah products in Islamic banking in Indonesia, against the background of complex modern economic challenges that require innovation of financial products according to sharia principles. The research aims to investigate the historical evolution and contemporary significance of Musharakah Mutanaqisha through tracing its conceptual origins from the time of the Prophet Muhammad to the period of Imam Mahzab, analyzing the transformation of Islamic economic thought in the development of modern fatwas, and examining the critical role of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) in promoting and implementing Islamic economic principles in the banking sector. Using a qualitative research method with a literature study approach, this study collects secondary data from primary sources such as DSN-MUI fatwas, Islamic legal texts, official documents of financial institutions, and secondary sources in the form of academic books, scientific articles, and research publications. Data collection techniques are carried out through systematic literature search, document analysis, and material categorization. Data analysis uses a qualitative content approach including descriptive, interpretive, comparative, and thematic analysis. The findings of the study show that the concept of Musharakah Mutanaqishah has undergone a significant evolution from the basic principles of help-help and capital cooperation during the time of the Prophet Muhammad to become an innovative solution in contemporary banking, with fatwa DSN-MUI No. 73/DSN-MUI/XI/2008 as an important milestone in providing the foundation of sharia law for financing products, although it still faces various obstacles such as limited legal regulations,  public perception, and human resources.